Romania - Functional Review : Health Sector - World Bank (Washington, DC, 2013)
This Functional Review was carried by a Bank team upon request by the Government of Romania. As a starting point, it shows that: (i) health outcomes in Romania lag behind those of the EU; (ii) users are not satisfied with its lack of responsiveness - long lines, informal payments, discourteous handling of patients, poor cleanliness, lack of maintenance, and breach of safety measures; (iii) the poor and other vulnerable groups (for example Roma communities) suffer from a significant lack of access to services; and (iv) the fiscal contraction of 2008-2010 exposed the weakness of financial controls in the health sector. The Review examines four health functions in depth: service delivery, financing, stewardship and resources (including pharmaceuticals). Based on our findings, we present recommendations categorized by the three set of challenges that the sector is facing: (i) improving governance and management; (ii) streamlining the health service network and re-launching quality control systems; and (iii) increasing preventive services and equity. For any expansion of the sector to be sustainable, a number of pre-requisites will need to be in place, including a private sector development strategy, stronger fiscal controls, a system of health technology assessment, and stronger management in key agencies.